Upgrade of the ATLAS Level-1 Trigger with event topology information. Issue 8 (December 2015) - Simioni, E.; Artz, S.; Bauβ, B.; Büscher, V.; Jakobi, K.; Kaluza, A.; Kahra, C.; Palka, M.; Reiβ, A.; Schäffer, J.; Schäfer, U.; Schulte, A.; et al.
Abstract: The Large Hadron Collider (LHC) in 2015 will collide proton beams with increased luminosity from 10 34 up to 3 × 10 34 cm −2 s −1 . ATLAS is an LHC experiment designed to measure decay properties of high energetic particles produced in the protons collisions. The higher luminosity places stringent operational and physical requirements on the ATLAS Trigger in order to reduce the 40MHz collision rate to a manageable event storage rate of 1kHz while at the same time, selecting those events with valuable physics meaning. The Level-1 Trigger is the first rate-reducing step in the ATLAS Trigger, with an output rate of 100kHz and decision latency of less than 2.5µs. It is composed of the Calorimeter Trigger (L1Calo), the Muon Trigger (L1Muon) and the Central Trigger Processor (CTP). By 2015, there will be a new electronics element in the chain: the Topological Processor System (L1Topo system). The L1Topo system consist of a single AdvancedTCA shelf equipped with three L1Topo processor blades. It will make it possible to use detailed information from L1Calo and L1Muon processed in individual state-of-the-art FPGA processors. This allows the determination of angles between jets and/or leptons and calculates kinematic variables based on lists of selected/sorted objects. The system is designed to receive and process up to 6Tb/s of real time data. The paper reports the relevant upgrades of the Level-1 trigger with focus on the topological processor design and commissioning.